In cellulo protein labelling with Ru-conjugate for luminescence imaging and bioorthogonal photocatalysis. Issue 93 (1st October 2015) - Sadhu, Kalyan K.; Lindberg, E.; Winssinger, N.
Abstract : Labelling of proteins with a luminescent ruthenium complex enables the direct visualization and photocatalytic reduction of aryl azide in live cells. Abstract : Labelling of proteins with a luminescent ruthenium complex enables the direct visualization and photocatalytic reduction of aryl azide in live cells. The confinement of catalysis to the labeled proteins was visualized using an azide-based immolative linker releasing a precipitating dye.